2015
DOI: 10.1158/1078-0432.ccr-14-3214
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RAS Membrane Association: Back to the Future for Anti-RAS Drug Discovery?

Abstract: RAS proteins require membrane association for their biological activity, making this association a logical target for anti-RAS therapeutics. Lipid modification of RAS proteins by a farnesyl isoprenoid is an obligate step in that association, and is an enzymatic process. Accordingly, farnesyltransferase inhibitors (FTIs) were developed as potential anti-RAS drugs. The lack of efficacy of FTIs as anti-cancer drugs was widely seen as indicating that blocking RAS membrane association was a flawed approach to cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
298
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(299 citation statements)
references
References 98 publications
(120 reference statements)
1
298
0
Order By: Relevance
“…FTase has been recently suggested as a drug target in the development of anti-cancer therapy (7,9). In the present study, it was demonstrated that FTI-277 exerted a more potent anti-proliferative effect on breast cells expressing an active mutant of H-Ras (H-Ras-MCF10A and Hs578T cells) than breast cells expressing wild-type H-Ras (MDA-MB-231 cells).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…FTase has been recently suggested as a drug target in the development of anti-cancer therapy (7,9). In the present study, it was demonstrated that FTI-277 exerted a more potent anti-proliferative effect on breast cells expressing an active mutant of H-Ras (H-Ras-MCF10A and Hs578T cells) than breast cells expressing wild-type H-Ras (MDA-MB-231 cells).…”
Section: Discussionmentioning
confidence: 57%
“…Farnesylation by FTase is the first irreversible, rate-limiting step for Ras membrane association and an obligate modification for oncogenic Ras biological activity (7). Initial attempts to inhibit FTase have been made in the development of anti-cancer agents (2,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The Kras gene encodes the protein of p21 RAS, which is a small GTPase that acts as a molecular switch by coupling cell membrane growth signals to intracellular signaling pathways and transcription factors to control multiple cellular processes (25,26). Oncogenically mutated RAS proteins fail to cycle "off" from the active, GTP-bound state to the inactive GDP-bound state, and thereby accumulated in the constitutive "on" configuration (27). Kras is the most common oncogene that has been found to be mutated in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of KRAS, this attachment requires the post-translational lipid modification of farnesylation (Cox et al 2015). While early efforts to target KRAS farnesylation have failed therapeutically, new small molecule inhibitors have been developed that instead target PDEδ, which binds to farnesylated KRAS and enhances its localization to plasma membranes (Chandra et al 2012;Zimmermann et al 2013).…”
Section: Targeting the Kras Pathwaymentioning
confidence: 99%